Effect of preoperative intranasal dexmedetomidine versus placebo on intraoperative shivering in parturients undergoing cesarean section: a randomized controlled trial - Xu, Guolin; Tian, Zhuhong; Ding, Yong; Ma, Jingjing; Li, Rui (Frontiers in Pharmacology, 2025)
BackgroundShivering during cesarean section under epidural anesthesia is common and may negatively affect maternal comfort, surgical conditions, and physiological stability. This single-blinded, randomized controlled trial evaluated whether preoperative intranasal dexmedetomidine reduces the incidence of shivering in parturients undergoing cesarean delivery.MethodsA total of 170 parturients scheduled for elective cesarean section under continuous epidural anesthesia were randomized into a dexmedetomidine group (group DEX) or control group (group CON). The group DEX received 1 μg/kg intranasal dexmedetomidine (diluted to 1 mL), and the group CON received 1 mL intranasal normal saline approximately 30 min before anesthesia. The primary outcomes were the incidence, severity, frequency, and duration of shivering. Neonatal safety was evaluated using Apgar scores at 1 and 5 min after delivery.ResultsA total of 160 patients completed the study. The incidence, frequency, severity, and duration of intraoperative shivering reactions were significantly lower in the group DEX than in the group CON (P < 0.01). Compared with those in the group CON, there were significantly more patients with level 2 sedation in the group DEX (P < 0.01). There were no significant differences in maternal hypotension, bradycardia, or nausea and vomiting events between the two groups (P > 0.01). There were no significant differences in Apgar scores between the two groups (P > 0.05).ConclusionPreoperative intranasal administration of dexmedetomidine effectively prevents intraoperative shivering in parturients undergoing cesarean section.Clinical Trial Registrationhttps://www.chictr.org.cn identifier: ChiCTR2400079811.